ANALISIS IMPLEMENTASI PARADIGMA KOGNITIVISME DAN HUMANISME DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Sabrun Jamil; Abdul Vickraam Makau; Inayah Rahmayani Mutmainnah; Nurul Hikmah; Rachel Amalia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the concepts, implementation, challenges, and solutions o the cognitivist and humanist paradigms in Islamic Religious Education. The background of this study is the gap between the ideal goals of Islamic Religious Education which emphasize cognitive development and character building and the actual learning conditions, which are influenced by differences in student abilities, limited learning resources, time constraints, and the impact of digital media. The objectives of this study are to describe the concepts of these two paradigms, analyze their implementation in Islamic Religious Education instruction, and identify the associated challenges and solutions. This study employs a qualitative approach using a literature review method. Data obtained from journals and previous studies were then analyzed using content analysis techniques. The results show that cognitivism emphasizes mental processes in learning, while humanism focuses on the holistic development of students’ potential. Both paradigms are implemented through student centered learning, with the teacher acting as a facilitator. The challenges arising in cognitivism and humanism can be addressed through differentiated instruction, scaffolding, enhancing teacher competencies, reflective learning, and continuous feedback.